Portrait of an agripreneur of India: An acceleration study - SHARMA, AKRITI; BHOOSHAN, NEERU; SINGH, AMARJEET; DESHMUKH, SAGAR S; PATRA, SRIKANTA P (The Indian Journal of Agricultural Sciences, 2019)
Entrepreneurship is a way to identify and fulfill a need by creating value for the stakeholders. There is a wide literature available to understand various aspects of entrepreneurship. Through rigorous search of literature, it was found that generally agri-entrepreneurship aka agripreneurship is being related with farm and rural enterprises only rather agripreneurship denotes entrepreneurship in all the areas that are related with agriculture and are a part of the agri produce supply chain. Hence an effort was made to portray an agripreneur of India who belongs to all these areas. For this, a data of 468 respondents was collected, who responded about the problems of agriculture they wish to solve, their business solution, target market and other factors that display the features and thought process of an agripreneur. The data was majorly qualitative in nature. Thematic content analysis was done with the help of Content Analysis Tool (CAT) and investigator triangulation was done to ensure reliability of the analysis. This research will help policymakers to design suitable policies for target people who aspire to venture into agriculture.